Performance and Carcass Production of Balinese Ducks Given Rumen Watse Based Biosupplement Rations - Dewi, Gusti Ayu Mayani Kristina; Sutama, I Nyoman Sutarpa; Wijana, I Wayan; Mudita, I Made (Advances in Tropical Biodiversity and Environmental Sciences, 2018)
A study aimed at studying the performance and production of Balinese duck carcasses that were given rations containing biosupplement-based waste of rumen content, conducted in the village of Peguyangan, Denpasar, Bali, for 3 months. Four biosupplements produced in this study were 1) BR 0 = biosupplement with fermented rumen based waste without bacterial isolates, 2) BR 1 = biosupplement with fermented rumen based waste with superior 1 cellulolytic bacteria inoculant  (BR 3.5 ), 3) BR 2 = biosupplement with fermented rumen based waste with superior 2 cellulolytic bacterial inoculants  (BR 3.3 ), 4) BRmix = biosupplement with fermented rumen based waste with combination of superior cellulolytic bacteria 1 and 2 (BR 3.5 and BR 3.3 ), The study was carried out with Completely Randomized Sampling/CR Design with 5 treatments and 3 repetitions, in which each repetition consisted of 5 Balinese ducklings aged 2 weeks. The treatment given was to ducks given supplemented ration with BR 0 ; BR 1 ; BR 2 ; BR mix , respectively for the treatment of R1; R2; R3; and R4, as well as ducks that were given basal rations without supplementation (R5). The results showed that the performance of duck that received treatment of R2 was significantly better (P<0,05) than R1, R3, R4 and R5, while the carcass butching weight and fat weight were not significantly different (P>0,05) . Based on the results obtained, it can be concluded; 1) the performance of Balinese ducks receiving ration biosupplement of R2 is better compared to R1, R3, R4 and R5; 2) Meat production/ducks carcasses to the weight of butchery, carcass production, non-carcass parts and body fats are not significantly real between all treatments.